Efforts to Strengthen and Protect Customary Land in Lampung - Muhammad Daffa Hakim (Jurnal Terekam Jejak, 2026)
Customary land for the Lampung Pepadun community has a meaning that is more than just an economic asset, but also reflects the identity, spirituality, and socio-cultural system inherent in the life of the community. In the Lampung Pepadun traditional view, land is "heritage land" that is passed down from generation to generation and managed by customary leaders based on the values ​​of Piil Pesenggiri and Sai Batin. However, to date, this customary land has not received formal recognition from the local government, making its legal status weak and vulnerable to takeover by outside parties. This study uses a normative juridical approach by examining the Basic Agrarian Law (UUPA) of 1960 and its various implementing regulations. The results show that the recognition of customary rights of indigenous communities is declarative, not constitutive, thus creating ambiguity in its implementation. In addition, obstacles faced by the Lampung Pepadun indigenous community include the lack of mapping of customary territories, weak public legal awareness, and overlap between customary law and national positive law. Therefore, regional regulations are needed that specifically recognize and protect the customary rights of the Lampung Pepadun community, with the active involvement of traditional institutions and the local government. Efforts to strengthen legal protection can be carried out through customary land registration, the integration of customary legal values ​​into land policies, and improving legal education for indigenous communities. With these steps, the protection of Lampung Pepadun's customary land can be realized in a just and sustainable manner in accordance with the principle of social justice mandated by Article 33 of the 1945 Constitution of the Republic of Indonesia.